2017
DOI: 10.4103/ijpsym.ijpsym_418_16
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Clinical Predictors of Response in Manic Episodes: A Naturalistic, Prospective, Cohort Study

Abstract: Background:Response to treatment of a manic episode is dependent on several sociodemographic and clinical factors as reported by researchers from other countries. The prescription of mood stabilizers and/or antipsychotics for manic episode depends on these factors. There is a lack of availability of data from India on this topic. Hence, this study was planned to identify the predictors of pharmacological response.Materials and Methods:Forty-two patients with a diagnosis of bipolar affective disorder current ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Different factors can explain the greater difficulty in obtaining clinical stabilization of psychotic versus non-psychotic bipolar patients, including more severity of illness at the time of admission to the hospital [ 44 , 45 , 46 ], the negative impact of the more numerous previous manic episodes [ 15 , 47 , 48 ] and the predominance of male gender that is more frequently characterized by comorbid substance use disorders [ 49 ]. Of note, some authors argued that bipolar women can have a better response to pharmacotherapy compared to men [ 50 ]. In addition, male hormones would favor the onset of psychotic symptoms in patients suffering from mood disorders [ 51 ], as revealed in previous studies, which showed that how higher dehydroepiandrosterone sulfate plasma levels could be associated with the presence of lifetime psychotic symptoms [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different factors can explain the greater difficulty in obtaining clinical stabilization of psychotic versus non-psychotic bipolar patients, including more severity of illness at the time of admission to the hospital [ 44 , 45 , 46 ], the negative impact of the more numerous previous manic episodes [ 15 , 47 , 48 ] and the predominance of male gender that is more frequently characterized by comorbid substance use disorders [ 49 ]. Of note, some authors argued that bipolar women can have a better response to pharmacotherapy compared to men [ 50 ]. In addition, male hormones would favor the onset of psychotic symptoms in patients suffering from mood disorders [ 51 ], as revealed in previous studies, which showed that how higher dehydroepiandrosterone sulfate plasma levels could be associated with the presence of lifetime psychotic symptoms [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%